Inequality and opportunity papers from the second ECINEQ society meeting - Bishop, John A.; Zheng, Buhong (Emerald, 2008)
Volume 16 of Research on Economic contains a selection of thirteen papers from the Second Biannual Meeting of the Society for the Study of Economic Inequality, Berlin, July, 2007. This conference brings together both established scholars in the field of income distribution as well as advanced graduate students and new Ph.D's. The multi-day conference provides a forum for over 150 participants to share their work with one another. The papers contained in this volume are selected from a few of the many different sub-fields represented at the conference. As the title suggests a major emphasis of the volume is to collect work on the inequality of opportunity. An additional emphasis of the volume is on inequality measurement issues. Finally, the volume is designed to present work from both senior researchers and as well as emerging scholars. The volume begins with an essay on equal liberties by Serge-Christophe Kolm. The second paper examines the relationship between inequality and envy. The next four papers address the inequality of opportunities. Empirical studies of the equality of opportunity include Africa, Italy, Germany, and the United States. The measurement section also contains four papers. The topics covered in these papers include welfare analysis with ordinal data, unit consistency and multidimensional inequality indices, unit consistency and intermediate inequality indices, and the examination of two newly rediscovered inequality measures originally introduced by Bonferroni and De Vergotini. The volume also includes papers on the intergenerational transfer of income inequality and poverty in the US and Germany, income inequality and mobility in Argentina, the use of experimental methods to understand inequality aversion, and the recognition that measuring unemployment is an ethical problem, not simply an exercise in statistical measurement.
Keywords: Equality -- Congresses.; Poverty -- Congresses.; elektronické knihy; electronic books